Constitutional and Judicial Interpretation of Environmental Laws in Nigeria, India and Canada - Nyekwere, Empire Hechime; Nnawulezi, Uche; Adiyatma, Septhian Eka; Balarabe, Kasim; Rouf, Muhammad Abdul (Lex Scientia Law Review, 2023)
The judiciary, an important branch of government responsible for legal interpretation, dispute resolution, and justice administration, holds a crucial role in national environmental protection. Courts play a key role in safeguarding a nation's environment by interpreting constitutional provisions related to environmental protection and other legislative frameworks. The effectiveness of a country's environmental protection is contingent on the assertiveness, creativity, and innovation of its judiciary in interpreting laws, policies, and regulations designed for environmental preservation. The widely held belief is that the judiciary, more than any other institution, is best positioned to adjudicate, inform, guide, and lead in environmental protection. A proactive, inventive, and inspirational judiciary motivates the executive and legislative branches to implement pertinent environmental laws, policies, and regulations. This study utilizes a doctrinal research methodology to comprehensively review and compare the environmental protection frameworks in Nigeria, India, and Canada. The focus is on constitutional provisions related to environmental protection and judicial interpretations, particularly in the context of Environmental Impact Assessment (EIA) laws. While explicit constitutional provisions on environmental protection are absent in Canada, India, and Nigeria, the courts in India and Canada have demonstrated creative interpretation of their constitutions to safeguard the environment. Notably, in India, environmental protection falls under the non-adjudicable Directive Principles of State Policy (DPSP).